2012
DOI: 10.1007/s11682-012-9180-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical signatures of cognition and their relationship to Alzheimer’s disease

Abstract: Recent changes in diagnostic criteria for Alzheimer’s disease (AD) state that biomarkers can enhance certainty in a diagnosis of AD. In the present study, we combined cognitive function and brain morphology, a potential imaging biomarker, to predict conversion from mild cognitive impairment to AD. We identified four biomarkers, or cortical signatures of cognition (CSC), from regressions of cortical thickness on neuropsychological factors representing memory, executive function/processing speed, language, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 68 publications
0
20
0
2
Order By: Relevance
“…However, biomarkers from multiple modalities examined together tend to predict cognitive decline better than any single biomarker (71; 82; 83; 85; 87; 89; 92; 95-97). Choosing appropriate biomarkers for the disease stage studied and consistently controlling for confounding covariates will empower future studies to more efficiently detect the effects of treatment and prevention efforts.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, biomarkers from multiple modalities examined together tend to predict cognitive decline better than any single biomarker (71; 82; 83; 85; 87; 89; 92; 95-97). Choosing appropriate biomarkers for the disease stage studied and consistently controlling for confounding covariates will empower future studies to more efficiently detect the effects of treatment and prevention efforts.…”
Section: Resultsmentioning
confidence: 97%
“…In most studies, the model that combined information from multiple modalities, including MRI, predicted decline better than any one biomarker alone (71; 82; 83; 85; 87; 89; 92; 95-97), underscoring the importance of tools flexible enough to accommodate information from multiple sources. Even so, several studies that examined multiple types of biomarkers found that baseline cognitive measures were the best single predictors of future conversion to AD (88; 90; 92-95).…”
Section: Predicting Cognitive Declinementioning
confidence: 99%
“…The first set of articles focused on the measurement of cognition and on improving reliability, sensitivity, and validity of measurements of different cognitive domains [449, 454, 464, 465]. A second set examined neuroimaging-cognition relationships [448, 453, 466], and a third set examined sequencing of biomarker and cognitive changes in relation to the model by Jack et al [14, 467, 468]. A final area examined genetic contributions to cognition using high-dimensional genetic data [469471].…”
Section: Studies Of the Adni Cohortmentioning
confidence: 99%
“…Prediction accuracy of the MCI to AD conversion was consistently lower by a similar degree in the ADNI setting, suggesting that these models are portable and robust in clinical settings. Gross et al [466] combined cortical thickness and cognitive data to predict MCI to AD conversion. They used regression analysis to develop cortical signatures of cognition specific to memory, executive function, language, and visuospatial processing domains, empirically defined by their correlation with domain-specific cognitive factor scores derived from new ADNI neuropsychological battery scores [112].…”
Section: Studies Of the Adni Cohortmentioning
confidence: 99%
“…Patients with AD exhibit memory impairment and cognitive decline due to neuronal loss mainly in the neocortex and the hippocampus [46]. AD currently affects over 36 million people worldwide with an estimated global economic impact of approximately $605 billion dollars in 2010 in addition to incalculable social and emotional burdens [47, 48].…”
Section: Td and Neurodegenerationmentioning
confidence: 99%